Comprehensive Sex Education: Holistic Approach to Biological, Psychological and Social Development of Adolescents - Danielle Fernandes; Mohita Junnarkar (Shiraz University of Medical Sciences, 2019)
Comprehensive sex education (CSE) aims to help youth gain a positive view of sexuality and appropriate knowledge to make healthy decisions about their sex lives. This report reviews CSE's holistic approach towards biological, psychological and social development. Relevant articles were gathered from Google Scholar and PubMed search engines, after applying inclusion criteria and screening papers. CSE proved to reduce STDs, pregnancy, delay sex initiation and promote safe sex. The psychological outcomes included decreased depression and increased self-esteem. CSE promoted healthy relationships and reduced discrimination around sexual orientation. Therefore, CSE programs support holistic youth development. This report recommends further research to correct inaccurate assumptions and increase support for CSE programs.